Health and poverty : global health problems and solutions - Walraven, Gijsbertus Engelinus Laurentius, 1957- (Earthscan, 2011)
Provides examples of diseases and problems related to health that disproportionally impact the poor, and gives their experiences a human face through individual case studies. Walraven provides a specific case study of a health problem, such as malaria, tuberculosis and HIV or health financing, including an introduction in each chapter followed by an historical review of the problem. From publisher description.